Coelacanth genomes reveal signatures for evolutionary transition from water to land - Nikaido, Masato (Cold Spring Harbor Laboratory Press, 2013)
Coelacanths are known as “living fossils,” as they show remarkable morphological resemblance to the fossil record and belong to the most primitive lineage of living Sarcopterygii (lobe-finned fishes and tetrapods). Coelacanths may be key to elucidating the tempo and mode of evolution from fish to tetrapods. Here, we report the genome sequences of five coelacanths, including four Latimeria chalumnae individuals (three specimens from Tanzania and one from Comoros) and one L. menadoensis individual from Indonesia. These sequences cover two African breeding populations and two known extant coelacanth species. The genome is ∼2.74 Gbp and contains a high proportion (∼60%) of repetitive elements. The genetic diversity among the individuals was extremely low, suggesting a small population size and/or a slow rate of evolution. We found a substantial number of genes that encode olfactory and pheromone receptors with features characteristic of tetrapod receptors for the detection of airborne ligands. We also found that limb enhancers of bmp7 and gli3, both of which are essential for limb formation, are conserved between coelacanth and tetrapods, but not ray-finned fishes. We expect that some tetrapod-like genes may have existed early in the evolution of primitive Sarcopterygii and were later co-opted to adapt to terrestrial environments. These coelacanth genomes will provide a cornerstone for studies to elucidate how ancestral aquatic vertebrates evolved into terrestrial animals.